Are multiple sclerosis patients and their caregivers more anxious and more committed to following the basic preventive measures during the COVID-19 pandemic? - Talaat, Farouk; Ramadan, Ismail; Aly, Salma; Hamdy, Eman (Multiple sclerosis and related disorders, 2020)
•MS patients were more anxious, depressed and stressed during the COVID-19 pandemic than their caregivers and the general population.•Younger patients, those with high EDSS scores and those who believed that MS patients are at high risk for COVID-19 infection were more anxious.•The patients’ knowledge about the factors that may affect the risk for COVID-19 infection was poor.•Though they were more anxious, they were not more committed – in contrast to what would be expected - to follow the basic preventive measures for staying safe during the pandemic than the general population. The novel coronavirus of 2019 (COVID-19), a pandemic of the kind not seen for a century, has caused global apprehension and distress. to evaluate whether the psychological state and behaviours of multiple sclerosis (MS) patients and their caregivers were different from the non-MS population or not during the pandemic. A cross-sectional survey was conducted on 115 MS patients, 33 MS caregivers and 129 healthy controls. Depression anxiety stress score-21 (DASS-21) was used for evaluation of their psychological state. MS patients had significantly higher DASS-21 scores (51.48±29.62) than their caregivers (29.79±27.19) and non-MS population (32.91±23.39) (p = 0.005). Younger patients (r=-0.252, p<0.0001), those with high EDSS scores (r = 0.023, p = 0.013) and those who believed that MS patients are at high risk for COVID-19 infection (p = 0.009) had the highest anxiety scores. There was no difference between the three groups in the level of commitment to staying at home (p = 0.747), wearing facemask (p = 0.164), wearing gloves (0.225), avoiding crowd (p = 0.225) and frequent hand washing (p = 0.570). Anxious patients had more relapses (p = 0.002) and pseudorelapses (p = 0.008). In this cohort, MS patients were more anxious, stressed and depressed during the COVID-19 pandemic than their caregivers and the non-MS population, but they were not more motivated to follow the basic preventive measures against infection.